(untitled) (Altre Modernità, 2021)
The subject of the wall, also in a symbolic sense, is a main topic in the works of the German playwright and film director Andres Veiel. Focussing on three films and a play realised between 2001 and 2011 (Der Kick, Black Box BRD and Wer wenn nicht wir), the essay illustrates how Veiel’s works intend to unmask and contribute to tear down walls of silence and fear in the German individual and collective memory. Moreover, the article points out how Veiel, while concentrating on the hidden structures behind terrorism and violence, intentionally chooses to use minimalist, sober and unspectacular aesthetics which take inspiration from the epic and documentary theatre.